O cicloturismo no caminho da fé - Roberto Marin Viestel (2023)
The objective of this doctoral thesis is to understand the cycle tourism that takes place on the Caminho da Fé, a 324 km pilgrimage route that begins in Águas da Prata/SP, crosses the Stats of São Paulo and Minas Gerais and ends at the Sanctuary of Our Lady Aparecida, in Aparecida/SP. Annually the shrine attracts millions of faithful; of these, the CF attracts thousands, with more than twenty thousand being tourists. We try to understand how cycle tourism has been taking place on this path (who does it, the motivations for cycle trips, which routes they take and how they do it); what place does the landscap occupy and how cycle tourists perceive it; what are the relationships that cycle tourists establish with spaces ; how leisure is expressed in the context of CF; and, finally, how cycle tourism has been developing. This research was carried out using a qualitative approach ; literature review; and, on-site cycle trips with more than 5.000 Kmm traveled in CF for observation between the years 2019 and 2022 (before, during ad « after » the COVID-19 pandemic). The data collection instruments were: field research diary; smartphone (voice and image capture); and, semi-structured interview; 27 cycle tourists were interviewed. The bicycle used was a TSW Super Light Alloy, Mountain bike Frame, Aluminum, 29 rim, disc and hydraulic brakes. The research results showed that the leisure practice of cycle tourism involves some particular characteristics, such as: physical preparation of cycle tourists; bicycle preparation and maintenance ; CF infrastructure; and, the different types of cycle tourism practices. The cycle trips revealed thar the cycle tourists motivations are linked to faith, but also to reasons that go beyond faith, such as tourism, excursions, the adventure of the unknown and cycle travel itself. The results also idicated the awakening of sensitive relationships of cycle tourists in relation to the geography of the path, in an experience of geographic reality in which the mountains proved to be elements that affect the organs of the senses, giving uniqueness to the CF and allowing the experimentation of a sensorial geography. Furthermore, we discoverd tha places and spaces affect cyclotourists sentimentally and give a symbolic uniqueness to a path that goes far beyond faith or things connected to the sacred, it goes towards the affective relationships thar are made possible by leisure on top of a bicycle.